Pengaruh Penempatan Kerja terhadap Kinerja Pegawai Pada Kantor Camat Megang Sakti Kabupaten Musi Rawas - Utami, Putri; Purnamasari, Endah Dewi; Handayani, Susi (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to evaluate the effect of job placement on employee performance at the Megang Sakti District Office, Musi Rawas Regency. This study uses a quantitative approach research method with a sample of 37 employees at the Megang Sakti District Office, Musi Rawas Regency. Based on the results of the study, it can be concluded that work placement does not have a significant effect on employee performance, job placement perceived by the employees of the Megang Sakti District Office, Musi Rawas Regency is considered high. The magnitude of the effect of work placement on the performance of the Megang Sakti District Office employees, Musi Rawas Regency is 4.8%. This shows that work placement has a low influence on employee performance. This research is expected to be an additional consideration to improve employee performance